The effect of rowing ergometer interval training on 2.4km performance - Chua, Hao Loong (Nanyang Technological University, 2021)
A high level of cardiovascular fitness (CVF) is often associated with longevity and health. Interval training is used to boost CVF levels,, however, the effect of different exercise modalities on interval training outcomes is unknown. Therefore, this study investigated the effect of rowing ergometer interval training on 2.4km performance. 20 male experienced dragon boaters aged 21-30 years old were recruited and divided into either the experimental group (EG) or control group (CG). All participants underwent a pre and post-test 5 weeks apart consisting of a body composition (DEXA) scan and a 2.4 km maximal effort run. EG had to undergo 8 interval training, with a work time of 12 minutes at 60-89% maximum heart rate and decreasing work-rest ratio over sessions scheduled at least 48 hours apart. Heart rate and RPE were collected after each repetition. Paired t tests were used to compare between the mean differences of participants’ 2.4km run time, fat mass, and fat-free mass. The 2.4 km time for EG improved significantly, t(8) = 6.66, p < .001, |d| = 2.22 as did that of CG, t(9) = 5.11, p <.001, |d| = 1.62). While EG significantly decreased fat mass, t(9) = 6.03, p < .001, |d| = 1.91, CG significantly gained fat mass, t(7) = -4.73, p = .001, |d| = 1.67. For fat-free mass, CG had no significant difference while the EG gained significantly, t(9) = -4.18, p = .002, |d| = 1.32. Overall, rowing ergometer interval training improves 2.4 km and body composition outcomes.